Factores de riesgos que influyen en enfermedades diarreicas agudas y su relación con la deshidratación en niños menores de 5 años, atendidos en el Centro de Salud de los Ángeles – Loreto en Quevedo, durante el segundo semestre del 2014 - Bajaña Zambrano, Lebida Esther (2015)
Diarrhoeal diseases are infections of the digestive tract caused by bacteria, viruses or parasites, whose main symptom is diarrhea, affecting 25% of children in Ecuador and causing death in children under five years by dehydration. More frequent in summer due to weather favors the spread of the bacteria that cause them are. With high temperatures, the risk of dehydration. It is estimated that globally diarrheal diseases affect more than 26% of children be a need to intensify actions aimed at reducing the incidence of intestinal infections and mortality thereof. This research work is quantitative because we worked with the sample was selected from the population treated at the Health Center of Los angels Loreto in Canton that Quevedo and descriptive data describing situations of acute diarrheal diseases in children was collected under 5 years. Quizás quisiste decir: Para conseguir datos de información, ejecuta encuestas a las pacientes entre 20 a 39 años que son atendidas en el Centro de Salud de Los Ángeles – Loreto en el cantón Quevedo, la cual mediante la tabulación de datos, arrojo como resultado que existe un 64% de madres que conocen acerca de las enfermedades diarreicas, mientras que el 28% de pacientes dicen desconocer sobre esta enfermedad que afectan a la mayoría de personas y más a los niños menores de 5 años de edad. To get information data, run surveys of patients between 20-39 years are treated at the Health Center of Los Angeles - Loreto in Canton Quevedo, which by tabulation, throw the result that there is a 64% mothers who know about diarrheal diseases, while 28% of patients say they know about this disease that affects most people and children under 5 years of age.This project was presented with the aim of informing about the risk factors influencing diarrhea, dehydration, causes, symptoms, complications. The results of this study allow us to apply the correct sanitary practices to prevent contagious diseases, always seeking the good life of citizens